Comparative morphological and biological studies of two rhagidiid mites: Robustocheles deltacus and Rhagidia qaliubiensis - Abou-Awad, B.A.; El-Sawaf, B.M.; Reda, A.S.; Abdel-Khalek, A.A. (Acarologia, 2011)
International audience The two rhagidiid species: Robustocheles (R.) deltacus and Rhagidia (R.) qaliubiensis were able to develop successfully from egg to adult on different fungal diets, but failed to lay eggs. When they were reared on larvae of cotton springtail Lepidocenitus insertus (Hand.), larvae of housefly Musca domestica L. and immatures of the tydeid soil mite Tydeus aegyptiaca (Rasmy and El-Bagoury), they laid eggs. They passed through egg, larvae, proto-, deuto-, tritonymph and adult stages. The durations of the immature and adult stages, as well as life table parameters were determined. Feeding on L. insertus gave the highest reproductive rate as compared to that on M. domestica and T. aegyptiaca. Ontogenetic setal development in the comparative study of the life stages of the two rhagidiid species indicated that the dorsal idiosomal chaetotaxy and the number of anal setae remained unchanged throughout the life cycle; a single adanal pair appears only in R. (R.) qaliubiensis protonymph and its successive stages. The increase in genital flap length at each moult is accompained by an increase in the number of setae situated on the flaps and the number of setae provides the simplest method of separating the nymphal stages. Patterns of leg chaetotaxy and solenidia also provide a method to separate nymphal stages.